Approximation of Common Fixed Points for a Finite Family of Uniformly Quasi-Lipschitzian Mappings in Banach Spaces: Yuchao Tang, Jigen Peng - Team, Support (Thai Journal of Mathematics, 2010)
The purpose of this paper is to study the su±cient and necessary condition on the strong convergence of the multistep iterative sequences with errors for a finite family of uniformly quasi-Lipschitzian mappings in Banach spaces. Our results extend and improve some recent results in the literature.